A Classification for Gastric Outlet Obstruction in Childhood: Extending Beyond Infantile Hypertrophic Pyloric Stenosis - Gürkan, Ödül Eğritaş; Öztürk, Hakan; Kaya, Cem; Kaya, Neslihan Gürcan; Bozbulut, Neslihan Ekşi; Can, Ayşe; Ceylan, Kamercan; Ünlüsoy Aksu, Aysel; Teker Düztaş, Demet; Sarı, Sinan; et al. (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Gastric outlet obstruction (GOO) is a rare condition in childhood, with the exception of infantile hypertrophic pyloric stenosis (IHPS). However, no classification exists from a pediatric gastroenterologists perspective. Materials and Methods: The patients with a diagnosis of GOO between 2009 and 2020 were reviewed retrospectively. We classified the patients according to GOO: presence of clinical findings accompanied by radiological and/or endoscopic findings; clinical status: intractable nonbilious postprandial vomiting alone or with abdominal pain, early satiety, weight loss, postprandial abdominal distension, and malnutrition; radiology: delayed gastric emptying and dilated stomach; endoscopy: nonbilious gastric contents after 6-8 hours of emptying and/or failed pyloric intubation; physical examination: visible gastric peristalsis. Results: A total of 30 GOO patients (15 patients with IHPS, 1 patient with annular pancreas, 4 patients with gastric volvulus, 2 patients with duodenal atresia, 2 patients with antral web, 1 patient with late-onset hypertrophic pyloric stenosis (LHPS) had surgical treatment, and remaining 5 patients had medical treatment) were enrolled to the study. The median age was 8 months (range: 3 months-16 years), and 14 patients were female. Mitochondrial disorders, LHPS, metabolic disorders, and eosinophilic gastrointestinal system diseases were added to Sharmas GOO classification, and the classification has been expanded. Conclusion: This is the first and largest study of GOO in children. From the perspective of pediatric gastroenterology, new diseases will be addressed, and definitions will be highlighted with our classification for GOO in childhood. Cite this article as: Eğritaş Grkan ö, öztrk H, Kaya C, et al. A classification for gastric outlet obstruction in childhood: Extending beyond infantile hypertrophic pyloric stenosis. Turk J Gastroenterol. 2024;35(3):255-261.